I AM NOT READY FOR TEACHING! EFL GRADUATES’ CHALLENGES AND EXPECTATIONS OF THE PROFESSION - Meddour, Mostefa (PEOPLE: International Journal of Social Sciences, 2017)
Every school year, Algerian Ministry of Education recruits hundreds of university Masters’ graduates to occupy job vacancies in teaching English both in Middle and Secondary schools. However, student teachers who eventually become novice teachers are often blamed of being unprepared and unqualified for the profession. Student teachers alike express their dissatisfaction with the quality of teacher education they have received and the lack of training in different areas of teaching. This exploratory paper seeks to investigate the level of readiness and preview the forecasted challenges that university graduates of English may encounter as they enter the school life. To do so, a questionnaire was administered to 136 Masters’ graduates of English at Biskra University to survey their major challenges and expectations of the teaching profession. The results revealed that a considerable number of student teachers are reluctant to join schools as they feel ill-equipped and untrained to become teachers though they see teaching as a promising job for the future. They also express their need to have pre-service teacher training sessions along their studies in which core elements of teaching need to be practiced and simulated especially lesson planning, classroom management and teaching language skills. The surveyed student teachers expressed their uncertainties of dealing with learners’ discipline problems in large classes especially in Secondary Schools, and preparing lessons from a textbook they have never trained to work with. For better insights into novice teachers’ challenges, a classroom observation-based enquiry and one-on-one interviews with beginning teachers may reveal further difficulties and suggest better recommendations.